Effects of the Thyroid Endocrine System on Gonadal Sex Ratios and Sex-Related Gene Expression in the Pufferfish Takifugu rubripes - Yuan, Zhen; Shen, Xufang; Yan, Hongwei; Jiang, Jieming; Liu, Binwei; Zhang, Lei; Wu, Yumeng; Liu, Ying; Liu, Qi (Frontiers in Endocrinology, 2021)
To examine the effect and mechanism of thyroid hormone on gonadal sex differentiation, Takifugu rubripes larvae were treated with goitrogen (methimazole, MET, 1000 ug/g), and thyroxine (T4, 2nM) from 25 to 80 days after hatching (dah). Gonadal histology and sex ratios of fish were then determined at 80 dah. MET treatment induced masculinization, but T4 treatment did not induce feminization in T. rubripes larvae. Transcriptomic analysis of gonads at 80 dah was then conducted. Among the large number of differentially expressed genes between the groups, the expression of foxl2, cyp19a1a, and dmrt1 was altered. The expression of foxl2, cyp19a1a, dmrt1 and gsdf at 25, 40, 55 days after treatment (dat) was further analyzed by qPCR. MET treatment suppressed the expression of foxl2 and cyp19a1a, and induced the expression of dmrt1 in genetic females (p < 0.05). Additionally, T4 treatment induced an increase in the expression of cyp19a1a in genetic XY gonads only at 25 dat. However, the increase in cyp19a1a expression did not continue to 40 and 55 dat. This may explain why feminization of larvae was not found in the T4-treated group. Thus, the present study provides the first evidence that MET treatment causes masculinization in teleost fish. The effects of MET-induced masculinization in T. rubripes may act primarily via suppression of the expression of foxl2 and cyp19a1a, and stimulation of the expression of dmrt1. Moreover, the effects of higher concentrations of T4 or different concentrations of T3, on sex differentiation require further testing.